Dual improvement in acid and redox properties of the FeOx/OAC catalyst via APS oxygen-functionalization: High low-temperature NH3-SCR activity, SO2 and H2O tolerance. (1st June 2023) - Li, Simi; Huang, Yan; Zhu, Hong; Long, Jiaqi; Xiao, Ling; Li, Pan; Zhao, Lingkui; Zhang, Junfeng
Graphical abstract: Highlights: Regulation of acid-redox properties over FeO x /OAC1.5-60-3 via APS oxygen-functionalization is designed and achieved. Fe valence and oxygen vacancy in FeO x /OAC1.5-60-3 are tailored based on the metal-support interaction. Fe dispersion, surface acidity and redox ability of FeO x /OAC1.5-60-3 have remarkably improved. FeO x /OAC1.5-60-3 shows high LT-SCR activity and resistance to H2 O and SO2 poisoning. Abstract: Carbon-based transition metal catalysts (CTCs) have shown tremendous potential within NO x abatement, while the improvement of low-temperature NH3 -SCR activity and SO2 and H2 O tolerance remains challenging. Herein, we report an easily-achievable strategy to regulate the active phases of the FeO x /AC catalyst via APS oxygen-functionalization for improving in acid and redox properties and facilitating NH3 -SCR activity. For redox sites, APS oxygen-functionalization boosted the metal-support interaction, immobilized γ-Fe2 O3 nanoparticles highly dispersed on FeO x /OAC1.5-60-3 surface. Meanwhile, Fe valence and oxygen vacancy of FeO x were tailored by APS oxygen-functionalization, resulting in the formation of active oxygen vacancy-coupled Fe 2+ . For acid sites, in situ DRIFTs further confirmed that APS oxygen-functionalization enhanced the adsorption and activation properties of NH3 over the oxygen-containing functional groups (OCFGs) on FeO x /OAC1.5-60-3. Due to the improvement of acid and redox properties, FeO x /OAC1.5-60-3 delivered superior NO conversion (>90 %) at 120–250 °C and SO2 /H2 O resistance in comparison with FeO x /AC. Therefore, this work sheds light on a robust and pragmatic strategy for the rational design of CTCs and provides a new insight in improving catalytic performance of CTCs.